Organizational Commitment and Employee Performance during the COVID-19 Pandemic: Evidence from a BPO Company - Ma. Elena C. Estebal; Joemy Lopez; Alan Dean (Research Synergy Foundation, 2024)
The pandemic necessitated remote workplace setup, and as employees’ homes doubled as their workplaces, it became difficult to distinguish between the two. With this reality came the challenge of enhancing employee performance and organizational commitment. This study investigated the correlation between organizational commitment and employee performance during the COVID-19 pandemic. This study involved 158 employees of a BPO (Business Process Outsourcing) company situated in Quezon City, Philippines. Non-parametric statistical testing such as Mann–Whitney U and Kruskal-Wallis tests were employed to examine the significant differences in the respondent's ratings when their demographic profiles were considered. Spearman’s rank correlation was used to measure the strength of the relationship between the constructs of organizational commitment and dimensions of employee performance. Results of the study revealed a high positive relationship between continuance commitment and employee performance. Furthermore, this study also explored organizational commitment along four demographic variables, resulting in the detection of significant differences in the perception of continuance commitment on account of gender, age, civil status, and length of service. A significant difference was also detected in affective commitment considering the length of service. Single, married, and widowed respondents also differed in their opinions on normative commitment. While research on organizational commitment exist, few studies have explored the role of demographic factors in shaping employee responses to pandemics. This study demonstrates value by examining the influence of demographic variables on organizational commitment and employee performance during the pandemic, adopting an intersectional perspective, and offering practical implications for organizational management, theoretical advancement, and future research directions.